The Specific Mechanism of TREM2 Regulation of Synaptic Clearance in Alzheimer’s Disease - Qin, Qi; Wang, Meng; Yin, Yunsi; Tang, Yi (Frontiers in Immunology, 2022)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease. Synaptic dysfunction is an integral feature of AD pathophysiology and a significant factor in early cognitive impairment in AD. Microglia, which are intrinsic immune cells in the central nervous system, play important regulatory roles in the process of synapse formation. Microglia can refine synaptic connections through synaptic clearance to ensure accurate synaptic transmission. Synaptic clearance is not only existed during central nervous system development but also aberrantly activated during AD pathology. However, the mechanisms of synaptic clearance in AD remain to be investigated. TREM2 is involved in the synaptic clearance of microglia, acting alone or with other molecules, such as apolipoprotein E (APOE). In addition, C1q is essential for microglia-mediated synaptic clearance. In this review, we systematically summarized the potential mechanisms of microglia involved in synaptic clearance, comprehensively reviewed the role of TREM2 in microglia regulating synaptic clearance and proposed our hypothesis that TREM2 interacts with APOE and C1q to promote synaptic clearance. This review provides new insights into the role of TREM2 regulation in microglia synaptic clearance and provides potential prospects for the treatment of AD.